Effect of artificial diet supplemented with antibiotics and antimicrobial peptides on silkworm (Bombyx mori L.) - Watthanarat, Phonphan; Bunchasak, Chaiyapoom; Phonphoem, Wannarat; Promboon, Amornrat; Ninpetch, Uraiwan; Kiewwong, Samrit; Wongpanya, Ratree (Agriculture and Natural Resources, 2026)
Importance of the work: Understanding the effects of antibiotics and antimicrobial peptides (AMPs) in artificial diets is crucial for silkworm growth, gut microbiota and disease prevention. Objectives: To examine the effects of antibiotics and AMPs on silkworm growth, development and survival during the first-to-third instars. Materials and Methods: Silkworms (Bombyx mori L.) were reared under controlled conditions and fed artificial diets containing antibiotics (amoxicillin) and AMPs. The diets were prepared using mulberry leaf powder, soy protein, vitamins and other ingredients. Biological parameters (survival rate, larval weight and development) were recorded and analyzed using Duncan’s test for significance. Four artificial diet formulations were evaluated: control (no antibiotics or AMPs), antibiotics (4%) and AMPs (0.2% and 0.4%). Results: Survival rates during the third instar differed significantly (p < 0.01): control (45.98%), antibiotics (38.16%), AMP 0.2% (21.74%) and AMP 0.4% (3.55%). In the second instar, the control and antibiotic groups had the highest weights (0.09 ± 0.01 g), significantly (p < 0.01) higher than AMP 0.2% (0.07 ± 0.01 g) and AMP 0.4% (0.06 ± 0.01 g). In the third instar, there was a significant (p < 0.05) difference only between the control group (0.28 ± 0.02 g) and the AMP 0.4% (T4, 0.09 ± 0.03 g). Based on these results, an antibiotic-free and AMP-free diet was beneficial for silkworm health and growth. Main finding: An antibiotic-free and AMP-free artificial diet supported optimal silkworm growth by preserving gut microbiota integrity. This novel approach eliminated the need for antibiotics, with important implications in advancing animal dietary research and the silk industry.